Non-periodized and Daily Undulating Periodized Resistance Training on Blood Pressure of Older Women - Coelho-Júnior, Hélio J.; Gonçalves, Ivan de Oliveira; Câmara, Niels O. S.; Cenedeze, Marco A.; Bacurau, Reury F.; Asano, Ricardo Yukio; Santana, Jeferson; Caperuto, Erico; Uchida, Marco C.; Rodrigues, Bruno (Frontiers in Physiology, 2018)
The present study aimed at investigating the effects of a daily undulating periodization (DUP) and non-periodized (NP) resistance training programs on hemodynamic parameters of older women. Forty-two older women were randomized into one of the three experimental groups: NP, DUP, and control group (CG). Evaluations of the hemodynamic parameters occurred before, during and after the intervention. The exercise programs were performed twice a week over 22 weeks. NP and DUP groups were based on 3 sets of 8–10 repetitions in 9 exercises. In NP, the two exercise sessions were based on traditional strength training, which was performed at a Difficult intensity according to the rating of perceived exertion (RPE) method. In DUP, the first session was based on power resistance exercise, in which the concentric muscle contraction was performed as fast as possible at a moderate intensity based on RPE, while the second session was the same that was performed by NP. The findings demonstrated that diastolic blood pressure (90.4 vs. 76.2 mmHg) and mean arterial pressure (108.6 vs. 92.7 mmHg) were significantly reduced after NP, while no significant alterations were observed in DUP. Nevertheless, both training groups seem to have a cardio protective effect, since both training modes prevented the increase in HR reported in the experimental period in CG. In conclusion, our findings indicate that a 22-week NP resistance training program causes beneficial effects on hemodynamic parameters of older women. Trial Registration: NCT03443375.